(untitled) (AIUB Journal of Science and Engineering (AJSE), 2025)
This study explores the application of Lean Manufacturing tools to small and medium-sized textile firms in Sirajganj, Bangladesh, aiming to enhance productivity and operational efficiency. By integrating Lean methodologies such as 5S, Kaizen, Kanban, and ABC analysis, the research addresses critical inefficiencies in production processes, inventory management, and energy consumption. Utilizing advanced tools like AutoCAD for precise layout design and Arena simulation for workflow analysis, the project achieved significant improvements. Key outcomes include a 43% reduction in inventory holding costs, a 30% decrease in production cycle time, and over 10% energy cost savings through waste-heat and steam-condensate recovery systems. These results demonstrate that systematic implementation of Lean tools can transform traditional manufacturing systems into agile, sustainable, and cost-effective operations. The findings provide a blueprint for other textile manufacturers to follow, highlighting the potential for Lean Manufacturing to drive competitiveness and sustainability in the textile industry.